การสร้างนวัตกรรมทางการพยาบาลสำหรับพ่อแม่ในการดูแลเด็กปวยระยะสุดทายที่บาน Development of Nursing Innovation during End of Life Care at Home for Parents - ตั้งวรพงษ์ชัย, จินตนา; สุ่มเล็ก, สุพรรณี (วารสารพยาบาลศาสตร์และสุขภาพ, 2014)
The first step of this action research was to study the in-depth situation of caring conditions and fac-tors effecting children during end of life care at home. The key informants consisted of 15 terminally children ill admitted in a hospital in Khon Kaen and 15 parents or caregivers from their families caring for the children at the hospital. Data collection took the form of participatory observation and in-depth interview. Data analysis was done via frequency and percentage. Content analysis was performed for qualitative information. The results showed that care for children in the end of life stage at home was caring behavior which the child, parents or caregivers from their families participated. When patients exhibited moderately abnormal symptoms, they took care via observation and assessing abnormal symptoms and care according to their health condition. Furthermore the children partook in daily activity and psychological support. At the stage of serious symptoms, parents or caregivers from their families checked and assessed for the children symptoms, con-sulted within family related to care. And caring by children symptoms, daily activity caring, psychological and spiritual care, they also brought the children to hospital for palliative care. However sometimes they could not offer care as a result of their perspective. Thus from children’s health condition, the perception of the children during the end of life, capability of parents or caregivers. Support from families and social leading to developing nursing innovations during end of life care at home for parents.